The proposal of improvement PT line connection for side Bánová in Žilina city - Gogola, Marián (Doprava a spoje, 2008)
This paper aimed to present the recent status of PT service in side Bánová in Žilina. This side is characteristics with poor level of PT service. In order to find out some efficient solution, this paper presents a proposal of improvement PT connection for side Bánová. The approach is interesting with different way of solution, where the localization of points of interests is taking into account. For that reason a new routing is proposed which considers all aspects of transport network and citizens activities in order to determine a future framework for stabile PT demand.